Making economically sound confinement decisions: A response to the zedlewski thesis - Meyer, Peter B. (American journal of criminal justice, 1991)
This paper examines the economic costs and benefits of incarceration of criminals, elaborating upon and correcting flaws in Zedlewski’s 1987 claims that incarceration is a cost-minimizing crime prevention strategy. We use Bureau of Justice Statistics data to demonstrate gross errors in Zedlewski’s crude estimates. We find that the costs of incarceration are more than double the benefits in costs of crime avoided. We conclude that the cost-saving incapacitation effects of incarceration do not warrant either the current levels of imprisonment or any future increases.